High piezoelectric response and polymorphic phase region in the lead-free piezoelectric BaTiO3CaTiO3BaSnO3 ternary system - Wanwisa Janbua; Theerachai Bongkarn; Taras Kolodiazhnyi; Naratip Vittayakorn (My University, 2017)
A new coexistence phase compositions between rhombohedral, orthorhombic and tetragonal phase was identified in the (Ba,Ca)(Ti,Sn)O3 system.
Keywords: Orthorhombic crystal system; Tetragonal crystal system; Trigonal crystal system; Ternary numeral system; Lead (geology); Ferroelectric and Piezoelectric Materials